Moroccan migration in Belgium : more than 50 years of settlement - Timmerman, Christiane; Fadil, Nadia; Goddeeris, Idesbald, 1972-; Clycq, Noel; Ettourki, Karim (CeMIS migration and intercultural studies, 2017)
Moroccans are one of the largest and most debated migrant groups in Belgium. 'Moroccan Migration in Belgium' analyses diverse facets of this community from a multidisciplinary perspective and addresses the most relevant and some underexposed topics in the rapidly developing field of migration studies. Combining various academic disciplines and different research methods, the book offers a panoramic introspection into the dynamic nature of migration studies in general and Moroccan studies in particular. The contributions of established academics and young researchers will not only appeal to scientific peers working on this domain, but also to teachers, social workers, policy advisors and other interested people who work from close or afar with this minority group.